Gambaran Klinis Sindrom Cerebral Palsy Tipe Diskinetik - Kaltihennah Oktavia Frauprades (Jurnal Medika Hutama, 2021)
Dyskinetic cerebral palsy is a type of cerebral palsy that causes impaired motor and postural functions. This neurological disorder is one of the most common causes of permanent limitation of movement in children. The purpose of this literature review is to summarize the clinical presentations of patients with dyskinetic cerebral palsy. The method used in this paper is a systematic review of scientific articles that have been published in the last ten years. The results obtained in this literature review show the typical movement disorders found in dyskinetic cerebral palsy patients in the form of dystonia and choreoathetosis which can be accompanied by non-motor symptoms.